Development of An Integrated Surface and Sub-Surface Simulation Model in A Single Simulation Platform - Zainal, S A; Daud, W R; Rosli, M I; Harun, S; Adi Putra, Zulfan; Bilad, M R (Universitas Pendidikan Indonesia, 2020)
An integrated model between surface and sub-surface is typically done by interconnecting many process modelling platforms. PROSPER and GAP are the common steady state modelling platforms for sub-surface while VMGSim and HYSYS are typical steady state surface modelling platforms. A major issue of using multiple simulation platforms is the compatibility of thermodynamic physical properties calculations among the platforms. This situation makes the simulations difficult to converge to a consistent thermo physical properties values. This is due to different interaction parameters applied in each platform that impact flashing and the physical property values even though the same property package such as Peng Robinson is used. To overcome this convergence problem, a single simulation platform within iCON (PETRONAS’s standard process simulation software, co-developed with VMG-Schlumberger) has been developed. This allows the use of one thermodynamic package across the integrated model. PROSPER sub-surface pressure-flow relationship results were automatically correlated and connected to surface models within the iCON environment. This integrated model was validated with data from operations and yielded about 1.23% average error tolerance. Based on this validated model, an optimization envelope can be developed with all possible well lineup configurations. This envelope covers set points for the operations where CAPEX free optimization can readily be applied.